Fundamentals of vehicle dynamics - Gillespie, Thomas D. (Warrendale, PA SAE International, 2021)
This book provides a clear and practical introduction to how vehicles move, focusing on the physics behind acceleration, braking, cornering, and ride. It explains key concepts like tire forces, weight transfer, suspension behavior, and handling characteristics in a way that's useful for automotive engineers and students. The revised edition includes updated examples and modern vehicle technologies.
Includes bibliographical references and index
Keywords: Công nghệ kỹ thuật ô tô